Energy consumption during impact cutting of canola stalk as a function of moisture content and cutting height - Mohsen Azadbakht; Ebrahim Esmaeilzadeh; Mostafa Esmaeili-Shayan (Journal of the Saudi Society of Agricultural Sciences)
This study surveys the needed energy for cutting canola stems in different levels of cutting height and moisture content. The canola was harvested from the experimental farm in Gorgan, Iran. Test device fabricated and then calibrated. The device works on the principle of conservation of energy. The tests were repeated 15 times for any level of moisture content and cutting height and they were analyzed using split plot design. The results showed the effect of height and moisture content on cutting energy is significant (P < 1%), but their interaction is not significant. The highest cutting energy was 1.1 kJ in 25.5 (w.b.%) moisture content and 10 cm cutting height. Also the minimum cutting energy was 0.76 kJ in 11.6 (w.b.%) moisture content and 30 cm cutting height. Blade velocity was 2.64 m/s in cutting moment.